FAKTOR-FAKTOR YANG MEMOTIVASI KECURANGAN LAPORAN KEUANGAN - Martdian Ratna Sari; M. Akhsanur Rofi (Research Center and Case Clearing House PPM School of Management, 2020)
Financial statements are an important instrument for every company. Financial statements are a window of information on the company's current financial condition. The function of financial statements is very important to make financial reports as a target of manipulation by individuals who have the intention to commit fraud. Not a few cases of financial statement fraud caused by pressure and opportunity factors that have actors. This study aims to analyze the effect of variables from the diamond fraud theory proposed by Wolfe and Hermanson (2004), namely financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, change in auditor, total accrual and capability of financial statements fraud proxied by the f-score model. This research focuses on state-owned companies because state-owned companies have enormous potential for fraud and corruption. In this study the sample used is 15 non-bank SOE companies that have been listed on the Indonesia Stock Exchange (IDX) in the 2011-2017 period. The type of data used is secondary data in the form of annual reports of BUMN companies that have been listed on the Indonesia Stock Exchange during the period 2011-2017. Hypothesis testing is done by using multiple linear regression methods. The results of this study indicate that the financial target variable which is proxied by return on assets is proven to have a positive effect in detecting financial statement fraud. The external pressure variable which is proxy by leverage ratio is proven to have a negative effect in detecting fraudulent financial statements. This study does not prove that financial stability, ineffective monitoring, nature of the industry, total accruals, change in auditors and capability have an influence in detecting financial statement fraud. The results of this study also prove that the factor that greatly influences the financial statement of fraud is the pressure factor. Therefore, it can be concluded that the variables in diamond fraud can be used in detecting financial statement fraud.